2016
DOI: 10.1016/j.cortex.2015.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Self-reference effect on memory in healthy aging, mild cognitive impairment and Alzheimer's disease: Influence of identity valence

Abstract: The self-reference effect (SRE) has been shown to benefit episodic memory in healthy individuals. In healthy aging, its preservation is acknowledged, but in Alzheimer's disease (AD), the jury is still out. Furthermore, there has yet to be a study of the SRE in amnestic mild cognitive impairment (aMCI). As self-reference implies subjective self-representations, and positive information enhance memory performance, we set out to examine the effects of 1) material and 2) identity valence on the SRE across the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 85 publications
(103 reference statements)
5
14
1
Order By: Relevance
“…The absence of SRE in our AD group corroborates results from previous reports of attenuated SRE and SRRE in AD (Genon et al, 2014a; Leblond et al, 2016), but extend these findings by using a source memory experimental design, showing neither item nor source memory enhancement. While a number of existing studies have demonstrated significant SRE and SRRE in AD (Kalenzaga & Clarys, 2013; Kalenzaga et al, 2013; Lalanne et al, 2013), the apparent disparity in results may be related to differences in methodological approaches.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The absence of SRE in our AD group corroborates results from previous reports of attenuated SRE and SRRE in AD (Genon et al, 2014a; Leblond et al, 2016), but extend these findings by using a source memory experimental design, showing neither item nor source memory enhancement. While a number of existing studies have demonstrated significant SRE and SRRE in AD (Kalenzaga & Clarys, 2013; Kalenzaga et al, 2013; Lalanne et al, 2013), the apparent disparity in results may be related to differences in methodological approaches.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, the relationship between the SRE and alterations in concept of self represents an important area of future enquiry, especially considering the marked changes to personality and interpersonal conduct in bvFTD (Piguet et al, 2011). While previous studies in AD have used self-rated measures of identity valence and certainty (Lalanne et al, 2013; Leblond et al, 2016), inclusion of measures that allow comparison between self and informant responses is necessary, as loss of insight is a prominent clinical characteristic in bvFTD (Piguet et al, 2011). Furthermore, given that we employed a region-of-interest approach in our VBM analyses, we could not exclude the possibility that atrophy of regions beyond the CMS may have also contributed to the reduced SRE in bvFTD and AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there have been very few studies of the SRE in aMCI. Rosa, Deason, Budson, and Gutchess (2015) found no SRE for trait adjectives in aMCI, whereas a study by Leblond et al (2016) found a SRE in aMCI that was specific to positively valenced trait adjectives. Another study by Rosa, Deason, Budson, and Gutchess (2016), indicated that individuals with aMCI did not show a benefit to source memory for selfreferenced items, although they did show overall better memory for items that were learned through self-related processing.…”
Section: Self-reference Effectmentioning
confidence: 93%
“…These authors showed that encoding information in relation to the self involved "deeper" processing than other encoding manipulations (such as those based on semantic knowledge or identification of surface details) and promoted episodic memory to a greater extent than other ways of encoding. Studies of the SRE have since been primarily conducted in young adults, but more recently the effect has been shown for trait adjectives in healthy aging (Carson, Murphy, Moscovitch, & Rosenbaum, 2016;Genon et al, 2014;Glisky & Marquine, 2009;Gutchess, Kensinger, Yoon, & Schacter, 2007;Lalanne, Rozenberg, Grolleau, & Piolino, 2013;Leblond et al, 2016). Given that healthy cognitive aging is associated with a decline in episodic memory, these results are encouraging.…”
Section: Self-reference Effectmentioning
confidence: 94%